2018
DOI: 10.1080/00016357.2018.1482421
|View full text |Cite
|
Sign up to set email alerts
|

Does dental agenesis have an impact on OHRQoL of children, adolescents and young adults? A systematic review

Abstract: Dental agenesis (DA) is defined as the congenital absence of teeth and is considered as the most common dental anomaly. It may cause speech and masticatory dysfunctions as well as esthetic problems. Its impact on oral health-related quality of life (OHRQoL) is not fully understood. The aim of the study was to assess whether DA affects OHRQoL of children, adolescents and young adults. A broad search was done on databases (Pubmed, Scopus, Web of Science and Virtual Health Library) using Medical Subject Headings … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 14 publications
0
16
0
1
Order By: Relevance
“…Considering that dental abnormalities in children affect chewing ability, pronunciation, facial appearance, and mental health, it is important to provide information on diseases with dental problems for pediatricians and dentists to effectively manage these patients. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…Considering that dental abnormalities in children affect chewing ability, pronunciation, facial appearance, and mental health, it is important to provide information on diseases with dental problems for pediatricians and dentists to effectively manage these patients. [ 7 , 8 ]…”
Section: Introductionmentioning
confidence: 99%
“…According to Locker et al, agenesis needs attention, and its impact on the well‐being and oral health‐related quality of life (OHRQoL) in individuals should be assessed. A few studies have investigated the impact of dental anomalies on OHRQoL …”
Section: Introductionmentioning
confidence: 99%
“…None of the selected articles had evaluated the impact on children and young adults, and only one article showed a greater impact of DA on adolescents with statistical significance in parameters within all OHRQoL domains. Therefore, it was concluded that evidence is insufficient to determine whether DA affects OHRQoL in children, adolescents, and young adults, and further studies are needed to clarify the unanswered question . This study aimed to test the hypothesis that DA impacts the OHRQoL of individuals.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations